Financial statement analysis - Subramanyam, K. R.; Wild, John J. (Boston, Mass. : McGraw-Hill/Irwin, 2007)
Emphasizes effective business analysis and decision making by various stakeholders of the company. This book begins with an overview, followed by accounting analysis and then financial analysis. It presents a balanced view of analysis, including both equity and credit analysis, and both cash-based and earnings-based valuation models
Includes bibliographical references (p. R1-R8) and index.
aia
Loans
Keywords: Financial statements; Financial analysis